KAJIAN CSR MELALUI SUDUT PANDANG PERENCANAAN TRANSAKTIF: STUDI KASUS PERENCANAAN CSR DI INDONESIA - Muhammad Taufiq; Suhirman Suhirman; Tubagus Furqon Sofhani; Benedictus Kombaitan (Universitas Agung Podomoro, 2019)
CSR gain local community development. However, its practice is contradictive, partially not only beneficial but also it does not bring significant benefits. CSR planning as an integration tool for the interest between corporate and local community is the main driving factor for its effectivity implementation. The article presents a communicative approach in CSR planning by combining both the concept of CSR and transactive planning. The general view that Corporate dominating CSR planning is the main criticism which causes its policy has not a significant impact. How is the conceptualization of CSR planning approach, which communicates with the beneficiary community, this article aims to reveal its understanding. The study evaluates the transactive process on CSR planning, through descriptive qualitative analysis of literature. The result proposes a CSR planning model based on transactive planning approach. The article also initiates that CSR planning is a transactive process which raised through knowledge transaction between planner and community toward towards legitimacy in increasing community support for company operations.